Macao as a brand: Can city branding change Macao’s image perceptions? - Carvalho, Marta Fevereiro (2015)
Competition between tourism destinations is becoming extremely fiercely as a result of the growing international tourism supply. Destinations are under constant pressure to attract visitors and promote cultural development, along with an ongoing necessity to raise the industry's quality standards. Destination image has been recognized as a key component for the success of the tourism management industry as it can influence traveler decision. Following this line of thought, the main goal of this dissertation is to explore the role that city branding plays on building Macao’s image perception on tourists and how it could be a competitive advantage to Macao. The research was conducted with the purpose of determining whether city branding can influence pre- and post-trip impressions held by foreigners regarding the image of Macao as a tourism destination.